2017
DOI: 10.1242/dev.146928
|View full text |Cite
|
Sign up to set email alerts
|

ID4 levels dictate the stem cell state in mouse spermatogonia

Abstract: Spermatogenesis is a classic model of cycling cell lineages that depend on a balance between stem cell self-renewal for continuity and the formation of progenitors as the initial step in the production of differentiated cells. The mechanisms that guide the continuum of spermatogonial stem cell (SSC) to progenitor spermatogonial transition and precise identifiers of subtypes in the process are undefined. Here we used an Id4-eGfp reporter mouse to discover that EGFP intensity is predictive of the subsets, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
196
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(225 citation statements)
references
References 45 publications
21
196
1
1
Order By: Relevance
“…Spermatogonial differentiation does not occur in mice treated with WIN 18,446 and consequently the testes become enriched with undifferentiated spermatogonia (Hogarth et al, 2013). Work of Helsel et al, 2017 demonstrated through functional transplantation analyses that the ID4-EGFP Bright population is essentially pure SSCs by 8 dpp. Here we found that ID4-EGFP Bright spermatogonia are enriched in the testis following WIN 18,446 treatment, suggesting an increased number of spermatogonia with stem cell potential, a possibility we confirmed by transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Spermatogonial differentiation does not occur in mice treated with WIN 18,446 and consequently the testes become enriched with undifferentiated spermatogonia (Hogarth et al, 2013). Work of Helsel et al, 2017 demonstrated through functional transplantation analyses that the ID4-EGFP Bright population is essentially pure SSCs by 8 dpp. Here we found that ID4-EGFP Bright spermatogonia are enriched in the testis following WIN 18,446 treatment, suggesting an increased number of spermatogonia with stem cell potential, a possibility we confirmed by transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Treated and control cell suspensions were then analyzed for EGFP intensity using a Cytoflex flow cytometer (B53000, Beckman Coulter, CA, USA) and the CytExpert Software (Beckman Coulter) to determine the percentage of ID4-EGFP+ and ID4-EGFP- cells. Additionally within the ID4-EGFP+ cells, the percentage of ID4-EGFP Bright, Mid, and Dim cells between treatments was measured as described previously (Helsel et al, 2017). The analysis was conducted at least 3 times from 3 different treated and control donor animals to achieve technical and biological replication.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3A). Based on the restricted pattern of expression, some have suggested that cells expressing ID4, PAX7 and/or BMI1 might be the ultimate spermatogonial stem cells (SSC ultimate ) (Helsel et al, 2017; Lord & Oatley, 2017; de Rooij, 2017). Indeed, the expression of each marker on functional stem cells has been confirmed by SSC transplantation and/or lineage tracing.…”
Section: Spermatogonial Stem Cells and Spermatogenic Lineage Develmentioning
confidence: 99%